Snack Attack! / Amy Michelle Segi … [et.al.] - Segi, Amy Michelle; Morris, Deborah; Atopia, Sherine; Minggan, Jackson Jalie; Nyarep, Nasheda Alencia (2018)
Our company's name is the SNACK ATTACK! in which this is business will be run in the form of partnership, which consists of 5 members. The business capital is RM35,000, which is from the contribution of RM7000 from every members. SNACK ATTACK ! is a convenient store but we specifically only sell various of snacks and beverages. We selected the well-known snacks and beverages from local and imported resources. As for the local brand, we sell YEOS, SEASON, F&N and MAGGIE. For the imported brand, we sell snack from Jack & Jill company and The Smith's Snackfood Company for Twisties. SNACK ATTACK ! is a snack shop that come with more than 10 types of brand for the snacks, beverages and instant food. The uniqueness of our snack shop are the services provided in our business where our business provides a cash-on-delivery services for our customer if they are unable to come to our premise. In addition, we are also provide a space for our customer if they want to have their meal on the spot.